Pulmonary Legionellosis in Oncologic Patients: Findings on Chest CT. Issue 6 (November 2016) - Shroff, Girish S.; Marom, Edith M.; Wu, Carol C.; Godoy, Myrna C.B.; Wei, Wei; Ihegword, Andrea; Han, Xiang-Yang; Truong, Mylene T.
Abstract : Objective: The purpose of this study was to report the computed tomography (CT) findings of non–pneumophila Legionella pneumonia and to compare these CT findings to those caused by Legionella pneumophila in oncologic patients. Methods: Chest CT scans of 34 oncologic patients with culture-proven Legionella infection (16 L. pneumophila and 18 non–pneumophila Legionella ) were retrospectively reviewed. Radiologic checkpoints included consolidation, ground-glass opacities, cavitation, nodules, tree-in-bud opacities, septal thickening, pleural effusions, and adenopathy, as well as the halo, reversed halo, and bulging fissure signs. Results: The most common imaging feature of Legionella pneumonia was consolidation, seen in 94% of patients. Ground-glass opacities were the next most common abnormality. The halo sign was present in 26% of patients, in both immunocompetent and immunosuppressed hosts. Most features occurred with similar frequency between L. pneumophila and non–pneumophila Legionella . Conclusions: Findings in L. pneumophila pneumonia and non–pneumophila Legionella pneumonia are similar but nonspecific. Airspace consolidation is almost always present; the halo sign is not uncommon.